LncRNA Gm26917 regulates inflammatory response in macrophages by enhancing Annexin A1 ubiquitination in LPS-induced acute liver injury - Zhao, Qing; Sheng, Meng-Fei; Wang, Yao-Yun; Wang, Xing-Yu; Liu, Wei-Yi; Zhang, Yuan-Yuan; Ke, Tiao-Ying; Chen, Shu; Pang, Gao-Zong; Yong, Liang; Ding, Zhan; Shen, Yu-Jun; et al. (Frontiers in Pharmacology, 2022)
Long noncoding RNAs (lncRNAs) are defined as transcripts of more than 200 nucleotides that have little or no coding potential. LncRNAs function as key regulators in diverse physiological and pathological processes. However, the roles of lncRNAs in lipopolysaccharide (LPS)-induced acute liver injury (ALI) are still elusive. In this study, we report the roles of lncRNA Gm26917 induced by LPS in modulating liver inflammation. As key components of the innate immune system, macrophages play critical roles in the initiation, progression and resolution of ALI. Our studies demonstrated that Gm26917 localized in the cytoplasm of hepatic macrophages and globally regulated the expression of inflammatory genes and the differentiation of macrophages. In vivo study showed that lentivirus-mediated gene silencing of Gm26917 attenuated liver inflammation and protected mice from LPS-induced ALI. Furthermore, mechanistic study showed that the 3’-truncation of Gm26917 interacted with the N-terminus of Annexin A1, a negative regulator of the NF-κB signaling pathway. We also found that Gm26917 knockdown suppressed NF-κB activity by decreasing the ubiquitination of Annexin A1 and its interaction with NEMO. In addition, expression of Gm26917 in inflammatory macrophages was regulated by the transcription factor forkhead box M1 (FOXM1). LPS treatment dramatically increased the binding of FOXM1 to the promoter region of Gm26917 in macrophages. In summary, our findings suggest that lncRNA Gm26917 silencing protects against LPS-induced liver injury by regulating the TLR4/NF-κB signaling pathway in macrophages.